2017
DOI: 10.1371/journal.pone.0185640
|View full text |Cite
|
Sign up to set email alerts
|

Host transcriptional responses following ex vivo re-challenge with Mycobacterium tuberculosis vary with disease status

Abstract: The identification of immune correlates that are predictive of disease outcome for tuberculosis remains an ongoing challenge. To address this issue, we evaluated gene expression profiles from peripheral blood mononuclear cells following ex vivo challenge with Mycobacterium tuberculosis, among participants with active TB disease (ATBD, n = 10), latent TB infection (LTBI, n = 10), and previous active TB disease (after successful treatment; PTBD, n = 10), relative to controls (n = 10). Differential gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…For instance, a study in Norway showed that LTBI was associated with increased serum levels of interleukin 1β, 6, and 22 and tumor necrosis factor α 22 . LTBI status was also associated with higher levels of monocyte/macrophage activation markers and chemo‐tactic mediators, such as CD14, 23 CXCL2, CXCL3, and IL8 24 . Another study reported a subtle increase in circulating interferon γ concentrations in persons with LTBI in the United States, compared with controls without LTBI 25 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study in Norway showed that LTBI was associated with increased serum levels of interleukin 1β, 6, and 22 and tumor necrosis factor α 22 . LTBI status was also associated with higher levels of monocyte/macrophage activation markers and chemo‐tactic mediators, such as CD14, 23 CXCL2, CXCL3, and IL8 24 . Another study reported a subtle increase in circulating interferon γ concentrations in persons with LTBI in the United States, compared with controls without LTBI 25 .…”
Section: Discussionmentioning
confidence: 99%
“…GBP2 is one of the prominent hubs in a highly active common core in TB [36]. Blocking CXCL2 could reduce the M. tuberculosis-induced IL-1β production [37,38]. Exposure of murine peritoneal macrophages to M. tuberculosis increases SLPI secretion and accelerates both the phagocytosis and killing of the pathogen [39][40][41], possibly by interacting with S100A8/A9 proteins to decrease lung tissue damage without affecting protective immunity against TB [42].…”
Section: Discussionmentioning
confidence: 99%
“…For example, CCR2 and its ligands MCP-1, MCP-2, and MCP-3, which recruit monocytes to the lung, are significantly increased upon M. tuberculosis infection (19, 29, 30). Similarly, mice lacking CD38, a sister molecule of CD157 with 33% homology in amino acid sequence, are highly susceptible to Mycobacterium avium without impaired immune cell recruitment to the lung (8).…”
Section: Discussionmentioning
confidence: 99%